Ranking up by moving out: The effect of the Texas Top 10% Plan on property values - Kalena E. Cortes; Andrew I. Friedson (Institute for the Study of Labor (IZA), 2010)
Texas engaged in a large-scale policy experiment when it instituted the Top 10% Plan. This policy guarantees automatic admission to their state university of choice for all high school seniors who graduate in the top decile of their high school class. We find evidence that households reacted strategically to this policy by moving to neighborhoods with lower-performing schools, increasing both property values and the number of housing units in those areas. These effects are concentrated among schools that were very low-performing before the change in policy; property values and the number of housing units did not change discontinuously for previously high-performing school districts. We also find evidence that these strategic reactions were influenced by the number of local schooling options available: areas that had fewer school choices showed no reaction to the Top 10% Plan.
Keywords: H31; H41; H73; I20; 330; Property values; college choice; affirmative action; Top 10% Plan; Bildungspolitik; Bildungschancen; Wirkungsanalyse; Wohnstandort; Hochschule; Bildungsverhalten; Immobilienpreis; Texas